2022
DOI: 10.54112/bcsrj.v2022i1.152
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Strategy for Mango Hopper Idioscopus Clypealis(lethierry) Management and Impact of Weather Factors on Its Population in South Punjab Pakistan

Abstract: Mango is an important, exportable fruit crop of Pakistan. Pakistan is occupying 6th position on the basis of mango production in almost 90 mango producing countries of the world. The mango hopper Idioscopusclypealis is a most destructive insect pest of mangoes in Pakistan. This pest may cause the economic loss to the mangoes due to due to its abundance and high population in dense traditionally managed mango orchards. Keeping in view the importance of the pest, a study was designed with an objective to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The association between total rainfall and hopper population was negative, although not statistically significant. According to [24] and [25], temperature was found to have a positive and substantial influence on the population of mango hoppers. Conversely, relative humidity was found to have a negative and significant impact.…”
Section: Seasonal Incidence Of Mango Hopper a Atkinsoni In Variety Of...mentioning
confidence: 99%
“…The association between total rainfall and hopper population was negative, although not statistically significant. According to [24] and [25], temperature was found to have a positive and substantial influence on the population of mango hoppers. Conversely, relative humidity was found to have a negative and significant impact.…”
Section: Seasonal Incidence Of Mango Hopper a Atkinsoni In Variety Of...mentioning
confidence: 99%
“…J., 2023:337. doi: https://doi.org/10.54112/bcsrj.v2023i1.337] 2 the resistance of fruits and vegetables to abiotic stress and helps prevent oxidative aging (Zaghum et al, 2022). Maintaining low temperatures during fruit storage is beneficial for delaying spoilage, inhibiting microbial growth, and minimizing metabolic variations (Ghaffar et al, 2022). However, certain products are susceptible to chilling injury and rapid deterioration when stored at temperatures below the chilling threshold (Iqbal et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Green and clean vegetative flushes ensures good yield by correcting fertiliser application in split doses, conversely yearly treatments may not be adequate, particularly on soils with high pH and calcareous characters (Zaghum et al, 2022), as these soils render nutrients inaccessible owing to nutrient fixation, volatilization and leaching losses (Iqbal et al, 2021b). As a result, applying nutrients at the correct time and in the right amount (Munir et al, 2022), while keeping crucial phenological stages in mind may be a valuable method for achieving good output on such soils (Ghaffar et al, 2022). Dubey et al, (2021) found a substantial link between leaf nitrogen content and yield, but no influence on leaf potassium contents.…”
Section: Introductionmentioning
confidence: 99%